2017
DOI: 10.4103/psychiatry.indianjpsychiatry_227_16
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of gratitude disposition promotion program on depression and quality of life of chronic schizophrenic patients

Abstract: Context:Gratitude intervention is expectedly an effective intervention to reduce depression and improve the quality of life in schizophrenic patients, but there is a lack of literature on it.Aims:We attempted to develop and test the effectiveness of the gratitude disposition promotion program for chronic schizophrenic patients in Korea.Settings and Design:Nonequivalent control group pre- and post-test design was used in two mental health centers located at Gyeonggi-do in South Korea.Materials and Methods:This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Similarly, the sample had a higher proportion of White participants and lower proportion of Black participants compared to the typical private psychiatric inpatient hospital in the United States, so findings may be limited to predominately White/Caucasian populations. However, there is some evidence that these findings might persist in less or differently religious settings and across diverse cultures and ethnicities given the persistent association between gratitude and suicide risk in samples outside the United States (Jung & Han, 2017;Lau & Cheng, 2017;Li et al, 2012;Lin, 2015;Ng & Wong, 2012;Rey et al, 2019;Varaee et al, 2019). Though far less numerous, international studies on patience also suggest the moderation by life hardships patience replicate across cultures (Hashemi et al, 2018;Valikhani et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the sample had a higher proportion of White participants and lower proportion of Black participants compared to the typical private psychiatric inpatient hospital in the United States, so findings may be limited to predominately White/Caucasian populations. However, there is some evidence that these findings might persist in less or differently religious settings and across diverse cultures and ethnicities given the persistent association between gratitude and suicide risk in samples outside the United States (Jung & Han, 2017;Lau & Cheng, 2017;Li et al, 2012;Lin, 2015;Ng & Wong, 2012;Rey et al, 2019;Varaee et al, 2019). Though far less numerous, international studies on patience also suggest the moderation by life hardships patience replicate across cultures (Hashemi et al, 2018;Valikhani et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…1.3.1 | Gratitude may protect through positive emotion, hope, and social relationships Previous work suggests gratitude is a protective factor for mental illness symptoms in highly distressed samples. Specifically examining psychiatric populations, a gratitude promotion program decreased depressive symptoms in patients with schizophrenia in South Korea (Jung & Han, 2017). Beyond this, few studies have examined gratitude among psychiatric inpatients, but numerous cross-sectional studies demonstrate the protective effects of gratitude against depressive and anxiety symptoms for potentially distressed samples, such as breast cancer patients in the United States (Ruini & Vescovelli, 2013), familial caregivers of persons with dementia in China (Lau & Cheng, 2017), trauma exposed college students in the United States (Van Dusen et al, 2015), and chronic pain patients in Hong Kong (Ng & Wong, 2012).…”
Section: Suicidality and Struggles With Meaningmentioning
confidence: 99%
“…Gratitude disposition was measured by the short version of the Gratitude Resentment and Appreciation Test (GRAT) (Thomas & Watkins, 2003;Watkins, Woodward, Stone, & Kolts, 2003). The Korean short version of GRAT has established reliability and validity (Jung & Han, 2017;Kim & Yi, 2009). The scale consists of 16 items scored on a 9-point Likert scale.…”
Section: Gratitude Dispositionmentioning
confidence: 99%
“…General and religious gratitude increased between admission and discharge, even though no direct interventions were undertaken to enhance gratitude. Several studies explored ways to increase gratitude in participants [6,7,9,18]. The most common approach was gratitude journaling intervention, whereby participants had to write down three to five things they were grateful for on a daily basis [5].…”
Section: Discussionmentioning
confidence: 99%
“…Yet only few studies on gratitude and depression have been conducted in clinical samples involving psychiatric patients. Previous studies have shown that patients with psychiatric disorders, such as depressions [6,7], schizophrenia [6], and suicidal tendencies [8], benefit from gratitude. In addition, gratitude modifies pathophysiological pathways, such as reducing inflammation in heart failure patients, lowering blood pressure, and improving immune function [9].…”
Section: Introductionmentioning
confidence: 99%